MENTAL HEALTH AS THE CORE OF INSTITUTIONAL WELL-BEING : THE ROLES OF INSTITUTIONAL LEADERS - Shukran Abdul Rahman, editor 611980; Aini Maznina A. Manaf, editor 651946 (Bandar Enstek, Negeri Sembilan : Akademi Kepimpinan Pendidikan Tinggi (AKEPT), 2023)
Since the COVID-19 pandemic hit the world in 2020, academic administrators, academic leaders and academics have put in various initiatives in finding ways to manage work-related issues as well as in addressing personal challenges, including issues that relate to mental health and well-being. International Islamic University Malaysia (IIUM) and Akademi Kempimpinan Pendidikan Tinggi (AKEPT) have made a collaborative effort in focusing on mental health issues which is one of the core components of institutional well-being. This book is written based on the topics presented in a one-day webinar on Mental Health as the Core of Institutional Well-Being: The Roles of Institutional Leaders with the theme "Promoting Mental Health among HLI Members" organised by AKEPT and IIUM. It discusses the issues related to memtal health experienced by the HLI community during the crisis, especially during the COVID-19 pendemic, and the practical suggestions and recommendations for HLIs in dealing with as well as managing the crisis.